The challenge of researching "partial exit" and "rootedness" among upper-middle classes in European cities. Issue 5 (28th May 2019) - Andreotti, Alberta; Le Galès, Patrick; Moreno-Fuentes, Francisco Javier
ABSTRACT: The rise of mobilities has paved the way for important changes within cities and the possibility for urban upper-middle classes to exit from their cities and national societies, disinvesting on them, while still taking profits in a process of deterritorialization with important consequences at the collective level. Investigating the extent to which upper-middle classes shaped and are still rooted (or not) in their cities is a challenge, even more when international comparison is involved. In this paper we focus on two methodological aspects: 1) the different social meaning that upper-middle classes and the social groups composing them can have considering three Western European countries and four cities: Paris, Lyon, Milan and Madrid. 2) How we generated our data through personal interviews with European managers, and the conceptual framework that informed the understanding of rootedness, exit or partial exit of our managers.